Navigating Comics: An Empirical and Theoretical Approach to Strategies of Reading Comic Page Layouts - Cohn, Neil (Frontiers in Psychology, 2013)
Like the sequence of words in written language, comic book page layouts direct images into a deliberate reading sequence. Conventional wisdom would expect that comic panels follow the order of text: left-to-right and down—a “Z-path”—though several layouts can violate this order, such as Gestalt groupings of panels that deny a Z-path of reading. To examine how layouts pressure readers to choose pathways deviating from the Z-path, we presented participants with comic pages empty of content, and asked them to number the panels in the order they would read them. Participants frequently used strategies departing from both the traditional Z-path and Gestalt groupings. These preferences reveal a system of constraints that organizes panels into hierarchic constituents, guiding readers through comic page layouts.